2015
DOI: 10.1117/12.2078972
|View full text |Cite
|
Sign up to set email alerts
|

A novel platform for minimally invasive delivery of cellular therapy as a thin layer across the subretina for treatment of retinal degeneration

Abstract: Incurable retinal degenerations affect millions worldwide. Stem cell transplantation rescued visual functions in animal models of retinal degeneration. In those studies cells were transplanted in subretinal "blebs", limited number of cells could be injected and photoreceptor rescue was restricted to areas in proximity to the injection sites. We developed a minimally-invasive surgical platform for drug and cell delivery in a thin layer across the subretina and extravascular spaces of the choroid. The novel syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This study and our previous work (Rotenstreich et al. ) suggest that the novel injection system may potentially be used for safe and efficient delivery of cell therapy and pharmaceuticals into the posterior pole, in close proximity to the target retina and choroid. Our platform may enable new, more efficient treatment for posterior segment diseases.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This study and our previous work (Rotenstreich et al. ) suggest that the novel injection system may potentially be used for safe and efficient delivery of cell therapy and pharmaceuticals into the posterior pole, in close proximity to the target retina and choroid. Our platform may enable new, more efficient treatment for posterior segment diseases.…”
Section: Discussionsupporting
confidence: 64%
“…In previous studies, we demonstrated the safety and efficacy of delivering stem cells into the EVSC compartment using this novel injector (Rotenstreich et al. ). In this study, we examined the efficacy and safety of delivering pharmaceuticals and nanotherapies into this compartment.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Transplanted cells were localized in a thin homologue layer, covering 87 ± 3% (mean ± SE) of the subretina surface 2 hours following transplantation [24, 25]. …”
Section: Resultsmentioning
confidence: 99%
“…This study established the rational for transplanting hBMSCs in the EVSC compartment as a possible treatment for AMD and RP. In subsequent studies, we demonstrated the efficient delivery of hBMSCs into the EVSC of rabbits using a novel injector [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%